Mechanical Properties of the Concrete Containing Porcelain Waste as Sand - Jamal, Mohammed; Noh, Mohammad Zaky; juboor, Shihab Al-; Wan, Mohd Haziman Bin; Takai, Zakiyyu Ibrahim (International Journal of Engineering and Technology, 2018)
The demand of concrete have been increases on a daily bases which consume a lot of natural resource such as sand and gravel,Â there is an immediate need for finding suitable alternative which can be used to replace sand partially with another materials with high proportion . Ceramic waste is one of the strongest research areas that include the activity of replacement in all the sides of construction materials. This research aims to improve the performance of concrete using ceramic waste, and demonstrate the performance of mechanical properties to the concrete with partial replacement of sand by using waste porcelain. For these, we analyzed the mechanical properties of the concrete such as compressive strength, split tensile and flexural strength, the specimen were measured based on 10% ,20% ,30% ,40%, and 50% weight ratio of replace sand with waste porcelain at different time under water for 7 days , 28 days , 60 days . The optimum consideration were given to mechanical properties of the concrete, at different amount of ceramic waste as sand.